Confirmatory Factor Analysis, Reliability, and Validity of Relational Maintenance Strategy Measure among Couples in Tehran - Mehdi Ghezelseflo; Nasim Aghamiri; Nasrin Aghamiri; Somayeh Hemati-Pouya (Shahid Beheshti University of Medical Sciences, 2018)
Background and Objective: Relationship maintenance Strategy has been described as the behavioral dynamics that assist in preserving a relationship. The aim of this study was to examine confirmatory factor analysis, reliability, and validity of relational maintenance strategy measure of couples in Tehran. Materials and Methods: This descriptive study with correlational design was conducted with participation of 420 couples with children who were studying in the first grade of high school in Tehran. Cluster random sampling was used for selecting participants. Data were collected by Relational Maintenance Strategy Measure (RMSM) and Marital Adjustment questionnaire. Construct validity and convergent validity were used to validate the questionnaire, and to test the reliability of the questionnaire, Cronbach's alpha and retest reliability coefficient were used.  Data were entered into AMOS-22 and SPSS-22 software and analyzed using Chi-square indices, Good fit indicators and Pearson correlation coefficient. Results: The mean (SD) age of participants was 37.6 (6.8). Cronbach's alpha coefficient of subscales assurance, openness, conflict management, share task, positivity, advice, social network, and total Relational Maintenance Strategy were 0.92, 0.91, 0.84, 0.79, 0.78, 0.80, 0.83 0.93, respectively. Correlation coefficients showed that RMSM had a significant positive correlation with DAS which indicates RMSM convergent validity (r= 0.54, P<0.01). In addition, factor structure of the scale of the investment model was confirmed using a confirmatory factor analysis (P<0.01). Conclusion: The study showed that the confirmatory factor structure, reliability and validity of the Relational Maintenance Strategy Measure were acceptable.